مدى توافر المعايير المادية والمالية - زين صالح السعدي, محمد (جامعة الوادي University of Eloued, 2018)
هدفت الدراسة إلى معرفة مدى توافر المعايير المادية والمالية في مدارس عدن الثانوية للموهوبين، واستخدمت الدراسة المنهج الوصفي التحليلي، وتكونت عينة الدراسة من جميع العاملين في مدارس عدن الثانوية للموهوبين (معلمين – إداريين)، البالغ عددهم (73) فرداً، وتوصلت الدراسة إلى نتائج أهمها: - حصل المحوران ككل على متوسط حسابي (1.27)، وانحراف معياري (0.25)، وكانت درجة توافر المعايير المادية والمالية بمدارس عدن الثانوية للموهوبين "قليلة جداً". - لا توجد فروق ذات دلالة إحصائية عند مستوى الدلالة (α≤0.05) بين استجابات أفراد عينة الدراسة تجاه مدى توافر المعايير المادية والمالية تعزى للمتغيرات (نوع المدرسة – المسمى الوظيفي – سنوات الخبرة في مجال الموهوبين). The objective of the research is to find out the availability of Standards for physical and financial standards in the Aden Secondary School for Gifted, and the research used descriptive analytical method, the sample consisted of all the workers in the typical Aden schools (teachers - administrative), the sample was (73) persons, and the research reached the following results: - The availability of human resources selection criteria in the Aden Secondary Schools for gifted (very few). -There are no statistically significant differences at the level of significance (α≤0.05) between the responses of the research sample members to the availability of standards physical and financial due to variables (type of school - job title – years of experience in the field of gifted).
في مدارس عدن الثانوية للموهوبين في الجمهورية اليمنية
مقال
Keywords: المعايير المادية والمالية، مدارس عدن للموهوبين; Physical and financial standards; Aden secondary school for Gifted